Prevalence of thyroid diffuse goiter and its association with body mass index and the presence of cysts and nodules in children and adolescents: the Fukushima Health Management Survey - Nana Nakahata; Mahiro Asano; Norikazu Abe; Haruka Ejiri; Hisashi Ota; Satoshi Suzuki; Ayako Sato; Rina Tazaki; Natsuki Nagamine; Chisato Takahashi; Yukie Yamaya; Manabu Iwadate; et al. (Endocrine Journal)
The main cause of diffuse thyroid goiter is autoimmune chronic thyroiditis, otherwise known as Hashimoto’s thyroiditis. Thyroid hormones play pivotal roles in growth and development during childhood. However, the prevalence of diffuse goiter and the relationships between diffuse goiter, thyroid volume, cysts and nodules, and anthropometric measurements in children are not well known. Among 789,459 participants who participated in thyroid ultrasound examinations, 320,206 participants (male: 161,728; female: 158,478) aged 1–23 years were analyzed. Logistic regression analyses were conducted to calculate the odds ratios of the standard deviation score of body mass index (BMI-SDS), the SDS of bilateral width multiplied thickness area (BWTAR-SDS) as a provisional determination of thyroid volume, and the presence of nodules or cysts for positive diffuse goiter compared with negative diffuse goiter after correction for sex and age. The prevalence of diffuse goiter increased in a female-dominant manner with aging. Compared with the absence of diffuse goiter, the age- and sex-adjusted odds ratios (95% confidence intervals) for BMI-SDS (1 SD), BWTAR-SDS (1 SD), cysts, and nodules were 1.24 (1.21–1.27), 3.21 (3.13–3.29), 0.53 (0.50–0.58), and 1.38 (1.17–1.64), respectively. The odds ratios of nodules for positive diffuse goiter were 4.18 (1.08–16.08), 1.76 (1.01–3.07), 1.80 (1.32–2.45), and 1.34 (1.08–1.67) in the age groups 1–7, 8–11, 12–15, and 16–23 years, respectively. The age-dependent increase in the prevalence of diffuse goiter was independently associated with increased BMI and positive prevalence of nodules in young individuals.